Sexualities in anthropology a reader - Weston, Kath 1958- (Blackwell anthologies in social and cultural anthropology, 2011)
"This thought-provoking new collection, Sexualities in Anthropology: A Reader offers insights into the diversity of human social beliefs and practices relating to sexuality in different times and in different cultures around the world. Substantial editorial introductions set each Part in context of the field, providing readers helpful background and explanatory notes. Presents a comprehensive collection of key historical and current readings in the social anthropology of sexuality Includes literature on both heterosexualities and same-sex sexualities Explores the key works and major debates of prominent scholars in the field, such as Mead, Malinowski, Newton , Herdt, and others Introduces readers to major theoretical developments ("essentialist" and "constructionist" positions)"--Provided by publisher.